Using ground penetrating radar to understand the failure of the Koh Ker Reservoir, Northern Cambodia. Issue 1 (29th August 2019) - Moffat, Ian; Klassen, Sarah; Attorre, Tiago; Evans, Damian; Lustig, Terry; Kong, Leaksmy
Abstract: Ground penetrating radar, probing, and excavation were used to create a contour map of the topography of a buried laterite pavement forming the spillway of a large abandoned reservoir at the Angkorian‐period city of Koh Ker in Cambodia. Calculations of the flow velocity of water through the spillway, based on the topography of the laterite surface, demonstrate that this outlet was even less adequate for passing the flow of water from the Stung Rongea catchment than had been estimated previously by Lustig, Klassen, Evans, French, & Moffat (2018). We argue that this design flaw contributed substantially to the failure of the reservoir's dike, possibly during the first rainy season after construction, which may have contributed to Koh Ker's remarkably short‐lived tenure as the political center of the Khmer Empire.